PENGARUH EFEKTIVITAS KERJA, KOORDINASI KERJA, DAN KUALITAS KERJA TERHADAP PERSEPSI KINERJA KARYAWAN DI PT. MATAHARI MEGAH - Chryzanta Farrelyn Halim; William Widjaja (Publika Citra Media, 2026)
Staff performance serves as a vital element in bolstering organizational efficiency. This investigation seeks to examine the impact of operational efficiency, team collaboration, and output standards on staff performance within PT. Matahari Megah. Employing a quantitative methodology, the study utilized a survey technique via questionnaires disseminated through the Google Forms platform. Primary data were gathered from 46 staff members employing a total sampling method. Statistical analysis involved multiple linear regression analysis using SPSS version 30, subsequent to conducting tests for validity, reliability, and classical assumptions. Findings reveal that operational efficiency, team collaboration, and output standards collectively exert a significant influence on staff performance. Individually, operational efficiency and team collaboration demonstrate a positive and significant relationship with staff performance, whereas output standards exhibit a positive yet non-significant association. These outcomes imply that enhancing operational efficiency and team collaboration holds greater prominence in boosting staff performance relative to output standards. The research yields theoretical contributions by strengthening human resource management theories concerning process-related factors, alongside practical applications for organizations in formulating ongoing strategies to elevate staff performance.